Qualitative Screening and Activity Assay of L-asparaginase-Producing Fungi from Tempeh - Niva Tahyat; Yurnaliza; Liana Dwi Sri Hastuti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to isolate and determine the types of fungi in tempeh that are capable of producing the enzyme L-asparaginase and how the enzyme activity is produced. The following steps were taken: Fungi were isolated using the pour plate method with Potato Dextrose Agar (PDA) medium; morphological characterization of fungi was performed macroscopically and microscopically.The ability to produce asparaginase was assessed qualitatively using modified liquid M9 medium and quantitative assay of L-asparaginase activity with the Nessler reagent. Potential fungi were identified based on identification books. The results of fungal isolation from tempeh yielded of 7 fungal isolates. Qualitative selection of fungal isolates from tempeh capable of producing L-asparaginase resulted in 4 fungi capable of producing the L-asparaginase enzyme, indicated by a pink color change in the medium. Quantitative assay was performed using an enzyme activity test .The results of quantitative selection showed that the highest activity of L-asparaginase enzyme was found in fungal isolate with the code TP 3, reaching 16,386 U/mL, which has been identified macroscopically and microscopically and is classified as belonging to the genus Aspergillus. These findings indicate that fungi from tempeh have the potential to produce the enzyme L-asparaginase.